Pollinator Behaviour on a Food-Deceptive Orchid Calypso bulbosa and Coflowering Species - Juha Tuomi; Juho Lämsä; Lauri Wannas; Thomas Abeli; Anne Jäkäläniemi (The Scientific World Journal)
Food deception as a pollination strategy has inspired many studies over the last few decades. Pollinator deception has evolved in many orchids possibly to enhance outcrossing. Food-deceptive orchids usually have low pollinator visitation rates as compared to rewarding species. They may benefit in visitations from the presence (magnet-species hypothesis) or, alternatively, absence of coflowering rewarding species (competition hypothesis). We present data on pollinator visitations on a deceptive, terrestrial orchid Calypso bulbosa, a species with a single flower per plant and whose flowering period partly overlaps with rewarding, early flowering willows (Salix sp.) and later-flowering bilberry (Vaccinium myrtillus). When surveying inactive bumblebee queens on willows in cool weather, about 7% of them carried Calypso pollinia. Most common bumblebee species appeared to visit and thus pollinate Calypso. Bumblebees typically visited one to three Calypso flowers before flying away, providing some support for the outcrossing hypothesis. We conclude that, regarding the pollinations strategy, both magnet-species and competition hypotheses have a role in the pollination of Calypso, but on different spatial scales. On a large scale rewarding species are important for attracting pollinators to a given region, but on a small scale absence of competition ensures sufficient pollination rate for the deceptive orchid.